# Simplify cos(sin^-1(x)) | Simplify cos(arc sin x)

The value of cos(sin^-1(x)) or cos(arc sin x) is equal to $\sqrt{1-x^2}$. In this post, we will simplify the expression $\cos(\sin^{-1}(x))$.

## Simplify cos(sin-1(x))

We note that both $\cos(\sin^{-1}(x))$ and $\cos(arc \sin x)$ have the same value. Thus to find out the value of $\cos(\sin^{-1}(x))$ or $\cos(arc \sin x)$, let us put
$\theta=\sin^{{-1}} x$ $\cdots (\star)$

As $\theta=\sin^{{-1}} x$ and we have to simplify $\cos(\sin^{-1}(x))$, we need to find out the value of $\cos \theta$. From the above equation, we get that

$x=\sin \theta$, that is,

$\sin \theta=x$ $\cdots (\star \star)$

Now, we will apply the Pythagorean trigonometric identity $\sin^2 \theta+\cos^2 \theta =1$. From this identity, we have that

$\cos^2\theta = 1-\sin^2 \theta$

$\Rightarrow \cos \theta = \sqrt{1-\sin^2 \theta}$

$=\sqrt{1-x^2}$ putting the value of $\sin \theta$ from $(\star \star)$ ]

$\therefore \cos \theta =\sqrt{1-x^2}$

Now, put the value of $\theta$ from $(\star)$

So, $\cos(\sin^{-1}(x))=\sqrt{1-x^2}$. Thus, the formula of $\cos(\sin^{-1}(x))$ is $\sqrt{1-x^2}$.

Question 1: Find the value of $\cos(\sin^{-1}(0))$
Using the above formula, we have that $\cos(\sin^{-1}(0))=\sqrt{1-0^2}=1$.
Question 2: Find the value of $\cos(\sin^{-1}(1))$
Using the above formula, we have that $\cos(\sin^{-1}(1))=\sqrt{1{-1}^2}=0$.